2007
DOI: 10.1074/jbc.m610108200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Rat Lysyl Oxidase Gene Promoter

Abstract: Lysyl oxidase (LO) stabilizes the extracellular matrix by crosslinking collagen and elastin. To assess the transcriptional regulation of LO, we cloned the 5-flanking region with 3,979 bp of the rat LO gene. LO transcription started at multiple sites clustered at the region from ؊78 to ؊51 upstream of ATG. The downstream core promoter element functionally independent of the initiator predominantly activated the TATA-less LO gene. 5 Deletion assays illustrated a sequence of 804 bp upstream of ATG sufficient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Comparative LO gene sequence alignment across species of rat, human and mouse showed that the proximal promoter region is highly conserved whereas the distal promoter region was more divergent among three species suggesting a fundamental role of the proximal promoter region in the regulation of LO transcription. The maximal promoter activities were detected in the 804, 808 and 924 base pair regions, respectively, immediately upstream of ATG in rat, mouse and human LO genes [59]. Thus, the LO transcription control is likely to be regulated by similar elements in these species.…”
Section: Lysyl Oxidasementioning
confidence: 99%
See 4 more Smart Citations
“…Comparative LO gene sequence alignment across species of rat, human and mouse showed that the proximal promoter region is highly conserved whereas the distal promoter region was more divergent among three species suggesting a fundamental role of the proximal promoter region in the regulation of LO transcription. The maximal promoter activities were detected in the 804, 808 and 924 base pair regions, respectively, immediately upstream of ATG in rat, mouse and human LO genes [59]. Thus, the LO transcription control is likely to be regulated by similar elements in these species.…”
Section: Lysyl Oxidasementioning
confidence: 99%
“…The INR and the DPE conserved in rat, human and mouse species coordinately function as a single core promoter unit for the RNA-Poly II-directed gene transcription [61]. It should be noted that the DPE in the rat LO gene promoter also worked as an independent core promoter module playing a key role in transactivation of the TATA-less LO gene at multiple transcription starts sites [59]. …”
Section: Lysyl Oxidasementioning
confidence: 99%
See 3 more Smart Citations